2017
DOI: 10.1590/0100-69912017002005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Telomerase (hTert), Ki67 and p16ink4a expressions in low and high-grade cervical intraepithelial lesions

Abstract: Objective : to study the association between the histological grading of cervical intraepithelial neoplasia (CIN I, CIN II and CIN III) and the immunohistochemical expression for p16ink4a, hTert and Ki67, as well as to evaluate the relationship of these markers with the risk of recurrence after surgical treatment. Methods : we studied a historical cohort of 94 women with intraepithelial lesions CIN I (low grade), CIN II and CIN III (high grades) submitted to conization or electrosurgical excision of the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Certain evidence indicated that spontaneous regression occurs in ~40% of cases of CIN2 ( 1 ), suggesting that these lesions probably have characteristics of being less aggressive compared to CIN3 or more severe lesions. The regression rate of CIN2 is similar to that of CIN1 in a 2-year follow-up period ( 2 ). At present, histopathological assessment is unable to differentiate high-grade CIN lesions from others and predict whether they may regress spontaneously.…”
Section: Introductionsupporting
confidence: 55%
“…Certain evidence indicated that spontaneous regression occurs in ~40% of cases of CIN2 ( 1 ), suggesting that these lesions probably have characteristics of being less aggressive compared to CIN3 or more severe lesions. The regression rate of CIN2 is similar to that of CIN1 in a 2-year follow-up period ( 2 ). At present, histopathological assessment is unable to differentiate high-grade CIN lesions from others and predict whether they may regress spontaneously.…”
Section: Introductionsupporting
confidence: 55%
“…Therefore, a predictive marker for CIN progression is crucial. The regression rates of CIN grades 1 and 2 were similar in the 2-year follow-up period [10,11]. Currently, histopathological assessment cannot differentiate high-grade CIN lesions from other lesions or predict whether they may regress spontaneously [10,11].…”
Section: Discussionmentioning
confidence: 89%
“…The regression rates of CIN grades 1 and 2 were similar in the 2-year follow-up period [10,11]. Currently, histopathological assessment cannot differentiate high-grade CIN lesions from other lesions or predict whether they may regress spontaneously [10,11]. Hence, certain prognostic biomarkers may be helpful in this differentiation [10,12].…”
Section: Discussionmentioning
confidence: 93%
“…The addition of further biomarkers in the multivariate model could balance these problems and stabilize the model. Along with to p16 INK4a , other cellular biomarkers such as Ki67, MCM2, Topo2α, and hTERT have been described as potential markers for cervical dysplasia detection, triage, and diagnosis [ 44 , 45 ]. Furthermore, there are more hrHPV genotypes that are responsible for CxCa development and could therefore be informative for dysplasia detection and characterization [ 4 ].…”
Section: Discussionmentioning
confidence: 99%